2003
DOI: 10.1080/1061186031000150791
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Drug Targeting--Biodistribution of the Magnetic Carrier and the Chemotherapeutic agent Mitoxantrone after Locoregional Cancer Treatment

Abstract: Magnetic Drug Targeting means the specific delivery of chemotherapeutic agents to their desired targets, e.g. tumors, by using magnetic nanoparticles (ferrofluids) bound to these agents and an external magnetic field which is focused on the tumor. This type of target directed drug injection attempts to concentrate a pharmacologic agent by enhancing its efficacy while simultaneously minimizing deleterious side effects. In previous studies, we have been able to demonstrate the efficacy of this type of localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Alexiou et al . have used mitoxantrone-loaded SPION and targeted them to VX2 squamous cell carcinoma in rabbits by using external magnets [177, 178]. MDT has also been used to improve localized drug delivery to interstitial tumor targets.…”
Section: Long-circulating Targeted and Stimuli-sensitive Nanocamentioning
confidence: 99%
“…Alexiou et al . have used mitoxantrone-loaded SPION and targeted them to VX2 squamous cell carcinoma in rabbits by using external magnets [177, 178]. MDT has also been used to improve localized drug delivery to interstitial tumor targets.…”
Section: Long-circulating Targeted and Stimuli-sensitive Nanocamentioning
confidence: 99%
“…A number of studies have demonstrated that magnetic nanoparticles (MNPs) can be magnetically targeted to tumor sites and the targeting effect has been assessed by various techniques, including optical imaging, magnetic resonance imaging (MRI) and histology studies (Prussian blue staining) [4], [5], [6], [7], [8], [9], [10], [11]. These studies have suggested that a higher concentration of magnetic therapeutic agents can be achieved upon the application of an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic targeting has recently emerged as a promising approach for localized retention of drug-loaded nanocarriers in tumor lesions [6, 7]. Studies in animal tumor models demonstrated that drug-loaded magnetic nanoparticles, injected directly into arterial blood supply of subcutaneous tumors, could be locally retained within the tumor tissue by an externally applied magnetic field [8, 9]. …”
Section: Introductionmentioning
confidence: 99%